The value of genome-wide analysis in craniosynostosis - Topa, Alexandra; Rohlin, Anna; Fehr, André; Lovmar, Lovisa; Stenman, Göran; Tarnow, Peter; Maltese, Giovanni; Bhatti-Søfteland, Madiha; Kölby, Lars (Frontiers in Genetics, 2024)
Background: This study assessed the diagnostic yield of high-throughput sequencing methods in a cohort of craniosynostosis (CS) patients not presenting causal variants identified through previous targeted analysis. Methods: Whole-genome or whole-exome sequencing (WGS/WES) was performed in a cohort of 59 patients (from 57 families) assessed by retrospective phenotyping as having syndromic or nonsyndromic CS. Results: A syndromic form was identified in 51% of the unrelated cases. A genetic cause was identified in 38% of syndromic cases, with novel variants detected in FGFR2 (a rare Alu insertion), TWIST1, TCF12, KIAA0586, HDAC9, FOXP1, and NSD2. Additionally, we report two patients with rare recurrent variants in KAT6A and YY1 as well as two patients with structural genomic aberrations: one with a 22q13 duplication and one with a complex rearrangement involving chromosome 2 (2p25.2 duplication including SOX11 and deletion of 2q22). Moreover, we identified potentially relevant variants in 87% of the remaining families with no previously detected causal variants, including novel variants in ADAMTSL4, ASH1L, ATRX, C2CD3, CHD5, ERF, H4C5, IFT122, IFT140, KDM6B, KMT2D, LTBP1, MAP3K7, NOTCH2, NSD1, SOS1, SPRY1, POLR2A, PRRX1, RECQL4, TAB2, TAOK1, TET3, TGFBR1, TCF20, and ZBTB20. Conclusion: These results confirm WGS/WES as a powerful diagnostic tool capable of either targeted in silico or broad genomic analysis depending on phenotypic presentation (e.g., classical or unusual forms of syndromic CS).